Methods of Research of Structural Adjustment of Economical Complex of Region - Ящеріцина, Н. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The following system of methods used to study the restructuring of the economic complex of the region ! general scientific methods (systematic approach, statistical, abstract-logical, literary, historical, structural analysis) and special methods (mapping, spatial analysis, balance sheet), which open and provide full information about the level of the economy from this region.